Shaping ability of TruNatomy, i-File X, and ProTaper Universal in mesial canals of 3D-printed mandibular molars: a micro-CT study - Wenyuan Zhou; Chao Liu; Ying Tang; Lu Wang; Yinfeng Qiu; Juan Fan; Lin Zhu; Zhigang Feng; Yongchun Gu (BMC Oral Health, 2026)
Abstract Background This ex vivo micro-CT study aimed to evaluate the shaping ability of three nickel-titanium (NiTi) rotary systems—TruNatomy (TN), i-File X, and ProTaper Universal (PTU) —in the mesial canals of three-dimensional (3D)-printed mandibular molars, with a focus on the effects of instrumentation on the danger zone. Methods Anatomical data were obtained through micro-CT scanning of two extracted mandibular first molar with moderately (Specimen 1) and severely curved mesial canals (Specimen 2). Each tooth was replicated into 18 models using a 3D printer. The resin tooth replicas ( n = 18) derived from each specimen were equally assigned to three groups ( n = 6 per group) to evaluate the shaping abilities of TN, i-File X, and PTU systems according to the manufacturer’s recommendations. The tooth replicas were scanned by micro-CT before and after instrumentation of the mesiobuccal (MB) and mesiolingual (ML) canals. Both moderately and severely curved canal models were evaluated. After 3D registration and reconstruction, canal straightening, changes in root canal volume and surface area, minimum mesial and distal canal wall thickness, and canal transportation at the levels 1, 2, 3, and 4 mm below the furcation were assessed. The data were analyzed by multifactorial ANOVA, followed by Tukey’s post hoc test. Results Across both groups of tooth replicas derived from Specimen 1 and Specimen 2, the use of TN and i-File X in the preparation of MB and ML canals resulted in significantly less canal straightening ( p < 0.05) and percentage increase in canal volume and surface area compared to the PTU system (all p < 0.05). The residual canal wall thickness and canal transportation were significantly affected by the severity of curvature (moderate/severe), root level, and the type of instrument used (all p < 0.01, multifactorial ANOVA). In most cases, following root canal preparation, the PTU group exhibited a significantly thinner remaining distal canal wall and greater canal transportation compared to the TN and i-File X groups for both sets of tooth replicas ( p < 0.05); while between the TN and i-File X groups, no statistically significant differences were generally found ( p > 0.05). Regarding the direction of canal deviation, at 1–2 mm below the furcation, all three instrument systems produced distal deviation. However, at deeper levels (3–4 mm below the furcation), the TN and/or i-File X systems showed a directional shift, with canal deviation occurring toward the mesial aspect. Conclusions 3D-printed tooth replicas provide a reliable platform for evaluating NiTi instrument performance in curved root canals and are well-suited for assessing the impact of canal preparation on danger zones of mandibular molars. The TN and i-File X systems showed comparable performance, demonstrating minimal canal transportation and preserving canal wall thickness in danger zones. In contrast, the PTU system was associated with significantly greater resin removal in danger zones and a greater tendency toward procedural errors in this ex vivo models.